2022
DOI: 10.1155/2022/2350522
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of COVID‐19 Infection in Students and Staff at a Private University in Thailand by Rapid SARS‐CoV‐2 Antigen Detection Assay

Abstract: The COVID-19 pandemic led to the suspension of all university courses which was followed directly by the implementation of online learning in Thailand. However, online learning was not suitable for all of Thailand. Rangsit University is a famous private university in Thailand and has been affected by this crisis, so it attempted to eliminate online learning by offering vaccination and antigen rapid screening tests to the students and staff who had to attend the university from July to September 2021. 93.71% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our study sample had a higher propor琀椀on of women, which was similar to that in other studies involving university medical students conducted in di昀昀erent countries 20,21 . However, no di昀昀erence was observed in the posi琀椀vity rates between the sexes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study sample had a higher propor琀椀on of women, which was similar to that in other studies involving university medical students conducted in di昀昀erent countries 20,21 . However, no di昀昀erence was observed in the posi琀椀vity rates between the sexes.…”
Section: Discussionsupporting
confidence: 86%
“…Our result was slightly di昀昀erent from those of other studies. It is due to the following factors: age of the inves琀椀gated par琀椀cipants; su昀케ciency of data collected from surveys or healthcare facili琀椀es; non-determina琀椀on of the severity of cases; whether any of the study par琀椀cipants were hospitalized; whether these events occurred during the 昀椀rst, second, or third wave of the disease; and vaccina琀椀on status of the par琀椀cipants 7,21,27,28,29,30 . These situa琀椀ons can alter an individual's percep琀椀on of reported symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The CDC reported that young people experience lower mortality rates compared with other age groups and typically exhibit mild disease symptoms [ 2 ]. During the COVID-19 vaccine rollout in Thailand, a study [ 18 ] conducted at a private university revealed that 1.18% of participants (comprising students and staff) tested positive for COVID-19 infection. According to this study, the majority of participants (> 80%) had already received COVID-19 vaccine, and it was observed that most infected persons were unvaccinated.…”
Section: Introductionmentioning
confidence: 99%